Students Code-switching and Code-mixing in Spoken Communication Activities at English Language Education Department of UIN Mataram - Muslihati Muslihati; Nurul Lailatul Khusniyah; Hery Rahmat (The Center for Language Development, Mataram State Islamic University., 2023)
The research aims to know the types of code mixing, the type of code switching and the factors of code-switching and code-mixing in the process of learning English in 6th semester students of the English Language Education department of UIN Mataram. This research was used descriptive qualitative approach. The subject of this study was one of the classes in the British American Australian course. The research applies observation, interviews and documents in collecting data. The study reveals that (1) there are 2 types of code mixing namely Insertion and alternation;(2) there are 2 types of code switching namely Intra-Sentential and Intra-Sentential; (3) there are 4 factors that cause students did code switching and code mixing in class namely situation, talking about a particular topic, difficulties to finding equivalent words in language in used, and intention of clarifying the speech content for interlocutor.